The gender gap reloaded: are school characteristics linked to labor market performance? - Spyros Konstantopoulos; Amelie F. Constant (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This study examines the wage gender gap of young adults in the 1970s, 1980s, and 2000 in the US. Using quantile regression we estimate the gender gap across the entire wage distribution. We also study the importance of high school characteristics in predicting future labor market performance. We conduct analyses for three major racial/ethnic groups in the US: Whites, Blacks, and Hispanics, employing data from two rich longitudinal studies: NLS and NELS. Our results indicate that while some school characteristics are positive and significant predictors of future wages for Whites, they are less so for the two minority groups. We find significant wage gender disparities favoring men across all three surveys in the 1970s, 1980s, and 2000. The wage gender gap is more pronounced in higher paid jobs (90th quantile) for all groups, indicating the presence of a persistent and alarming glass ceiling.
Keywords: J16; J24; J31; 330; wages; gender differences; school effects; quantile regression.; Lohndifferenzierung; Frauenarbeitslohn; Geschlechterdiskriminierung; Bildungsabschluss; USA